Exposure-in-vivo containing interventions to improve work functioning of workers with anxiety disorder: a systematic review - Nieuwenhuijsen Karen; Klingen Elmer F; van der Klink Jac JL; Noordik Erik; van Dijk Frank JH (BMC, 2010)
Abstract Background Anxiety disorders are associated with functional disability, sickness absence, and decreased productivity. Effective treatments of anxiety disorders can result in remission of symptoms. However the effects on work related outcomes are largely unknown. Exposure in vivo is potentially well fit to improve work-related outcomes. This study systematically reviews the effectiveness of exposure-in-vivo containing interventions in reducing work-related adverse outcomes in workers with anxiety disorders. Methods A systematic study search was conducted in Medline, Cinahl, Embase and Psycinfo. Two reviewers independently extracted data and from each study assessed the quality of evidence by using the GRADE approach. We performed a meta-analysis if data showed sufficient clinical homogeneity. Results Seven studies containing 11 exposure-in-vivo interventions were included. Four studies were focused on Obsessive Compulsive Disorder (OCD), two on Post Traumatic Stress Disorder (PTSD), and one on a mixed group of OCD and severe phobias. The studies were grouped according to type of anxiety disorder and subsequently according to type of comparisons. For OCD, exposure-in-vivo containing interventions can yield better work-related outcomes compared to medication (SSRIs) and relaxation but not better compared to response prevention. The results on anxiety outcomes were similar. The net contribution of exposure in vivo in two OCD intervention programs is also presented as a meta-analysis and shows significant positive results on work role limitations. The calculated pooled effect size with 95% confidence interval was 0.72 (0.28, 1.15). For PTSD, exposure-in-vivo containing interventions can yield better work-related and anxiety-related outcomes compared to a waiting-list but not better compared to imaginal exposure. Conclusions Exposure in vivo as part of an anxiety treatment can reduce work-related adverse outcomes in workers with OCD and PTSD better than various other anxiety treatments or a waiting-list. We recommend that it should be studied how the results of these studies can be transferred to the practice of occupational health professionals and how clinicians can make better use of them to improve work-related outcomes. In future research, priority should be given to high-quality randomised controlled trials (RCTs) in which exposure-in-vivo containing interventions are applied to a variety of anxiety disorders and compared with other clinical anxiety treatments such as SSRIs. Work-related outcomes, in particular work functioning and sickness absence, need to be assessed with reliable and valid measures.